Palladium-catalyzed direct intermolecular silylation of remote unactivated C(sp3)–H bonds. Issue 89 (20th October 2016) - Pan, Jin-Long; Li, Quan-Zhe; Zhang, Ting-Yu; Hou, Si-Hua; Kang, Jun-Cheng; Zhang, Shu-Yu
Abstract : An efficient and convenient method has been developed to achieve direct silylation of unactivated remote primary or secondary C(sp 3 )–H bonds to form C–Si bonds with hexamethyldisilane (HMDS). Abstract : An efficient and convenient method has been developed to achieve direct silylation of unactivated remote primary or secondary C(sp 3 )–H bonds to form C–Si bonds with hexamethyldisilane (HMDS). This method highlights the emerging strategy to transform unactivated methyl or methylene into versatile functional groups in organic synthesis and provides a new method to construct functionalized C–Si bonds for synthetic chemistry.